2017
DOI: 10.1007/s10237-017-0985-4
|View full text |Cite
|
Sign up to set email alerts
|

Flow perfusion rate modulates cell deposition onto scaffold substrate during cell seeding

Abstract: The combination of perfusion bioreactors with porous scaffolds is beneficial for the transport of cells during cell seeding. Nonetheless, the fact that cells penetrate into the scaffold pores does not necessarily imply the interception of cells with scaffold substrate and cell attachment. An in vitro perfusion system was built to relate the selected flow rate with seeding efficiency. However, the in vitro model does not elucidate how the flow rate affects the transport and deposition of cells onto the scaffold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Previous studies oriented their investigation on only CFD models for analyzing these type of variables that cannot be assessed by means of experiments [6][7][8][9][10][11]15,13,14,12]. Only recent works apply the FSI technique for studying the complex hydrodynamic environment within a scaffold [23,27,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies oriented their investigation on only CFD models for analyzing these type of variables that cannot be assessed by means of experiments [6][7][8][9][10][11]15,13,14,12]. Only recent works apply the FSI technique for studying the complex hydrodynamic environment within a scaffold [23,27,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) has been widely used for solving and determining the shear stress distribution of idealized [3,4] and complex microCT-based scaffold structures [5][6][7][8][9][10][11][12]. Recently, a validation of such models using particle image velocimetry (PIV) has been proposed with the aim of investigating how fluid flow conditions modulate cell motion and deposition during perfusion [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, good permeability of the scaffold, translated to the properties of the structure, means the right pore size distribution, high pore interconnectivity, and sufficient porosity [7,8,9]. Furthermore, permeability affects the magnitude of pressure and shear forces inside scaffolds, identified as potential stimuli for cellular differentiation or functional adaptation, for cell seeding efficiency and in vivo new tissue formation [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Cell marbles (0.5-2.0 mm in diameter) were produced by wrapping different types of cells suspended in culture media with electrospun nanofibers. Microscopic analysis of the CMs stored in mineral oil at room temperature for 10 minutes indicated that almost all of the initially encapsulated cells precipitated either at the bottoms of the CMs or on the up-inclined inner surfaces of the cloaks driven by gravity (Campos Marín et al, 2018;Scarritt et al, 2018).…”
Section: Discussionmentioning
confidence: 99%